Synthesis and Inhibitory Studies of Phosphonic Acid Analogues of Homophenylalanine and Phenylalanine towards Alanyl Aminopeptidases - Wanat, Weronika (Biomolecules, 2020)
A library of novel phosphonic acid analogues of homophenylalanine and phenylalanine, containing fluorine and bromine atoms in the phenyl ring, have been synthesized. Their inhibitory properties against two important alanine aminopeptidases, of human (hAPN, CD13) and porcine (pAPN) origin, were evaluated. Enzymatic studies and comparison with literature data indicated the higher inhibitory potential of the homophenylalanine over phenylalanine derivatives towards both enzymes. Their inhibition constants were in the submicromolar range for hAPN and the micromolar range for pAPN, with 1-amino-3-(3-fluorophenyl) propylphosphonic acid (compound 15c) being one of the best low-molecular inhibitors of both enzymes. To the best of our knowledge, P1 homophenylalanine analogues are the most active inhibitors of the APN among phosphonic and phosphinic derivatives described in the literature. Therefore, they constitute interesting building blocks for the further design of chemically more complex inhibitors. Based on molecular modeling simulations and SAR (structure-activity relationship) analysis, the optimal architecture of enzyme-inhibitor complexes for hAPN and pAPN were determined.